Argentina and its relationship with the Russian Federation (2007-2023). The pursuit of international autonomy amidst a dynamic link - Ilivitzky, Matias Esteban (2024)
Objective/context: This paper aims to explore the links that some recent Argentine presidencies (Cristina Fernández de Kirchner, Mauricio Macri and Alberto Fernández) maintained with the Russian Federation.Methodology: It will initially dwell into the longstanding tradition of pacifism which characterizes Argentine foreign policy, and then proceed to register the strategy of its most recent federal administrations regarding their international outlooks and its ties with Russia. Its strategy regarding the war in Ukraine will be inscribed within that broader diplomatic framework and tradition. It will then introduce the concept ‘geopolitical vaccinationalism’ into this scenario, making connections between purely public health issues, originated after the outbreak of the COVID-19 pandemic, and foreign policy postures and decisions that are not necessarily related to them. In this section, the strategies of some recent Argentine administrations regarding the purchase of COVID-19 vaccines to be administered to its population will also be covered. Finally, in the last section of the paper, the issue of the increased rate of pregnant Russian women coming to Argentina to give birth will also be tackled.Conclusions/originality: This situation, prompted by the Russian-Ukraine Conflict, increased the strains between Presidents Alberto Fernández and Vladimir Putin, while also presenting risks in regard to the international standing of Argentina and the seriousness with which its passport is being regarded by foreign governments.